2018
DOI: 10.1186/s12943-017-0754-0
|View full text |Cite
|
Sign up to set email alerts
|

MiR-25-3p promotes the proliferation of triple negative breast cancer by targeting BTG2

Abstract: BackgroundTriple-negative breast cancer (TNBC) is highly invasive and aggressive and lacks specific molecular targets to improve the prognosis. MiR-25-3p promotes proliferation of many tumors and its role and underlying mechanisms in TNBC remain to be well elucidated.MethodsDifferential expression of miR-25-3p in TNBC was measured with quantitative real-time PCR (qRT-PCR) in both TNBC tissues and cell lines and was validated in the Cancer Genome Atlas (TCGA) database. The effects of miR-25-3p on proliferation,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
110
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 136 publications
(111 citation statements)
references
References 38 publications
1
110
0
Order By: Relevance
“…These findings suggest that miRNAs could become novel molecular targets for HCC treatment. The oncogenic roles of miR-25-3p in numerous types of cancers have previously been investigated (40,41). In HCC, one previous study demonstrated that miR-25-3p was upregulated in HCC tissues when compared with adjacent normal tissues and that the upregulation of miR-25-3p is of predictive value on poor prognosis (22).…”
Section: Discussionmentioning
confidence: 99%
“…These findings suggest that miRNAs could become novel molecular targets for HCC treatment. The oncogenic roles of miR-25-3p in numerous types of cancers have previously been investigated (40,41). In HCC, one previous study demonstrated that miR-25-3p was upregulated in HCC tissues when compared with adjacent normal tissues and that the upregulation of miR-25-3p is of predictive value on poor prognosis (22).…”
Section: Discussionmentioning
confidence: 99%
“…However, emerging studies have confirmed that different miRNAs play diverse roles in TNBC, some as tumorigenic agents, and some as tumor inhibitors. For example, as tumorigenic agents, miR-25, 16 miR-20, 17 miR-224, 18 miR-135 19 and miR-301 20 promote the occurrence and development of TNBC, whereas miR-124, 15 miR-4417, 21 miR-4306, 22 miR-199, 23 miR-1287 24 and miR-3178 25 as tumor inhibitors inhibit the oncogenesis and development of TNBC. In this study, relative miR-153 expression in TNBC tissues and cells was remarkably lower than that in corresponding adjacent noncancerous tissues and normal breast epithelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, other panels of upregulated miRNAs, such as miR-20a-5p, miR-25-3p, miR-135b, and miR-502, are associated with the proliferation of TNBC and cell lines by targeting different genes. The expression of B-cell translocation gene 2 (BTG2) is negatively regulated by miR-25-3p, and indirectly activates the AKT and ERK-mitogen-activated protein kinase (MAPK) signaling pathways to mediate the proliferation of TNBC cell [148]. MiR-20a-5p promotes TNBC cell proliferation by targeting the Runt-related transcription factor 3 (RUNX3), as well as its direct downstream targets, Bim and p21 [149].…”
Section: Mirnas In Cell Proliferation In Tnbcmentioning
confidence: 99%